O lugar da hermenêutica bíblica na formação teológica da igreja evangélica Assembleia de Deus - Oliveira, Sérgio Batista de (2012)
A hermeneutic analysis of IEAD (Igreja Evangélica Assembleia de Deus Evangelical Church Assembly of God) has been little discussedin dissertations and theses that deal with it. Therefore, our basic objective is to analyze what constitutes the Pentecostal theology present in IEAD,inquiring on what is the place of biblical hermeneutics in the theological formation of IEAD. With that in mind, we reflect here on this subject, aimingto understand the history of IEAD, its expansion in Brazil and its insertion in Pentecostalism, contemplating the analysis of the hermeneutic basis which underlies its theology. Methodologically, we will build an interpretative analysis of the few studies on that approach, ranging from authorswho have built a more religious study of the expansion of that movement, to thosewho have deepened their discussionsfrom an analysis of its administrative structure, while highlighting authors who turn specifically to other movements of Pentecostalnature which formed the basis of the theology of that religious group. As results obtained from research on previous movementsand the very IEAD, we highlight here the influence of Pahram and theologies present among Pietists, Methodists, Montanistsand the prosperity theology as well asthe way concordism has been presentin the literal interpretation of the Bible performed by that group.